Forklift Design Integrated Speed Limiter and Position Tracking Through IoT-Based Website - Khairansyah, Mades Darul; Nastiti, Vanny; Dwikurniawan, Yoga; Rahmawati, Mazida; Ardiansyah, Alvin (Faculty of Engineering, Universitas Tanjungpura, 2024)
Forklifts, as lifting and transportation equipment, play a crucial role in logistics. However, forklift operators often chase targets, pushing the forklift to perform at higher speeds. Operating a forklift at high speeds not only poses potential dangers to the working conditions but can also lead to a decrease in forklift performance. Operators do not ensure the forklift is running according to procedures due to a lack of supervision. In response to this issue, the author proposes an innovation in the form of a monitoring device capable of recording speed violations committed by operators. With the planned device, it is expected that forklift operators will exercise more caution and take greater responsibility when operating the forklift. The objective of this research is to reduce the likelihood of accidents and forklift damage due to improper use. The study produces a forklift design equipped with supporting components for the implementation of the device and a website as a monitoring platform for forklift operators and workers, providing real-time access to collected data. This system enhances operational safety in operating forklifts. The research significantly contributes to the development of safer and smarter forklift technology, aligning with strict demands for safety standards and risk management in industrial environments.